2008
DOI: 10.1099/ijs.0.65567-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny by a polyphasic approach of the order Caulobacterales, proposal of Caulobacter mirabilis sp. nov., Phenylobacterium haematophilum sp. nov. and Phenylobacterium conjunctum sp. nov., and emendation of the genus Phenylobacterium

Abstract: Phylogeny by a polyphasic approach of the order Caulobacterales, proposal of Caulobacter mirabilis sp. nov., Phenylobacterium haematophilum sp. nov. and Phenylobacterium conjunctum sp. nov., and emendation of the genus Phenylobacterium rRNA genes were determined for the genera Asticcacaulis, Brevundimonas, Caulobacter and Phenylobacterium and the description of the genus Phenylobacterium is emended.The genus Caulobacter was originally composed of dimorphic, prosthecate bacteria. In these prokaryotes, reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
56
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 31 publications
(21 reference statements)
6
56
1
Order By: Relevance
“…This fatty acid profile is similar to those of closely related type strains except for the considerable amount of summed feature 4 and the absence of the hydroxy fatty acids C 12 : 0 3-OH and C 12 : 1 3-OH that are the main hydroxyl fatty acids of the genus Phenylobacterium (Abraham et al, 2008). ECL 18.084 was only found in strain A8 T .…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…This fatty acid profile is similar to those of closely related type strains except for the considerable amount of summed feature 4 and the absence of the hydroxy fatty acids C 12 : 0 3-OH and C 12 : 1 3-OH that are the main hydroxyl fatty acids of the genus Phenylobacterium (Abraham et al, 2008). ECL 18.084 was only found in strain A8 T .…”
mentioning
confidence: 64%
“…The sequence similarity with 'Phenylobacterium zucineum' HLK1 was 97.8 %. Comparison of the 16S rRNA gene sequence of strain A8 T with those of other type strains of the genus Phenylobacterium revealed that strain A8 T was also missing nucleotides 71-88, 183-190, 206-211 and 452-476 (Escherichia coli numbering) (Abraham et al, 2008). Strain A8 T had 178-T, 1265-T and 1270-A, in agreement with P. composti 4T-6 T , P. immobile E T , P. koreense Slu-01 T , P. lituiforme Fail3 T , P. conjunctum FWC 21 T , P. haematophilum CCUG 26751 T and 'P.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the polar lipid analysis noted above and the recent characterization of novel species of Phenylobacterium (Abraham et al, 2008;Oh & Roh, 2012), genera of the family Caulobacteraceae can be distinguished by their composition of polar lipids. Among these genera, Asticcacaulis comprises prosthecate bacteria with, at the time of writing, four recognized species: Asticcacaulis excentricus (Poindexter, 1964), Asticcacaulis biprosthecium (Pate et al, 1973), Asticcacaulis taihuensis (Liu et al, 2005) and Asticcacaulis benevestitus (Vasilyeva et al, 2006).…”
mentioning
confidence: 99%